Highest Solar-to-Hydrogen Conversion Efficiency in Cu2ZnSnS4 Photocathodes and Its Directly Unbiased Solar Seawater Splitting - Abbas, Muhammad; Chen, Shuo; Li, Zhidong; Ishaq, Muhammad; Zheng, Zhuanghao; Hu, Juguang; Su, Zhenghua; Li, Yanbo; Ding, Liming; Liang, Guangxing (Nano-Micro Letters, 2025)
Despite being an excellent candidate for a photocathode, Cu2ZnSnS4 (CZTS) performance is limited by suboptimal bulk and interfacial charge carrier dynamics. In this work, we introduce a facile and versatile CZTS precursor seed layer engineering technique, which significantly enhances crystal growth and mitigates detrimental defects in the post-sulfurized CZTS light-absorbing films. This effective optimization of defects and charge carrier dynamics results in a highly efficient CZTS/CdS/TiO2/Pt thin-film photocathode, achieving a record half-cell solar-to-hydrogen (HC-STH) conversion efficiency of 9.91%. Additionally, the photocathode exhibits a highest photocurrent density (Jph) of 29.44 mA cm−2 (at 0 VRHE) and favorable onset potential (Von) of 0.73 VRHE. Furthermore, our CTZS photocathode demonstrates a remarkable Jph of 16.54 mA cm−2 and HC-STH efficiency of 2.56% in natural seawater, followed by an impressive unbiased STH efficiency of 2.20% in a CZTS-BiVO4 tandem cell. The scalability of this approach is underscored by the successful fabrication of a 4 × 4 cm2 module, highlighting its significant potential for practical, unbiased in situ solar seawater splitting applications. Highlights: 1 A novel approach, precursor seed layer engineering, is applied to prepare Cu2ZnSnS4 (CZTS) light-absorbing films using the solution-processed spin-coating method. 2 Mo/CZTS/CdS/TiO2/Pt photocathode effectively mitigates defects in CZTS light absorber and the CZTS/CdS heterojunction interface, optimizing charge carrier dynamics. 3 Record photoelectrochemical performance including half-cell solar-to-hydrogen (HC-STH) efficiency of 9.91%, photocurrent density of 29.44 mA cm−2 at 0 VRHE in 0.5 M H2SO4 electrolyte, and STH efficiency of 2.20% in CZTS-BiVO4 tandem cell in natural seawater is achieved.